Innovation Platforms as A Strategy to Support the Agricultural Innovation System in Indonesia: Case study on The Implementation of Jajar Legowo Super - Purwaningsih, Indah; Ayunda, Winda Anestya; Ariana, Lutfah (Jurnal Manajemen Teknologi, 2024)
Abstract. The strategy for utilizing research results through collaboration between stakeholders is crucial in developing agricultural innovation system. This study examines the multi-stakeholders collaboration on the scaling process of the Jajar Legowo (Jarwo) Super technological package as the research result of the Agricultural Research and Development Agency (Balitbangtan), Ministry of Agriculture (MoA), Indonesia. Employing the innovation platform framework, this study explores the multi-stakeholders’ perspectives by conducting semi-structured interview with related stakeholders: researchers, policy makers, disseminators, and local governments. The innovation platform framework is applied to map the actors, roles and functions that support the scaling process along the value chain from the problem identification, towards technology development through experimentation and the upscaling process in the system. The study finds that the innovation platform succesfully improve the rice productivity in some regions despite some challenges. Instead of full technology application, farmers prefer integratge them with indigenous practice due to the limited absorptive capacity, socio-economic background and natural conditions of the region. Also, the findings highlight the gap in multistakeholder relation despite the central rolef of the central government that not only act as a policy maker but also technlogy developer, disseminator, and logistic providers. The goverment is suggested to enhance the institutional arrangements by engaging industry in input logistic system to provide farmers’ access on technology supply and integrate policoes/programs with the local government and  other related stakeholders to accelerate the upscaling process. Keywords:  Agricultural innovation system; Innovation platform; Jajar legowo super; Multi-stakeholders collaboration, sclaing process